(untitled) (UNED Research Journal, 2020)
Introduction: Habitats disturbed by fragmentation and human activities increase the need to establish strategies to conserve species dependent on mature and continuous forests. Objective: To analyze the composition of insectivorous understory birds in three habitats with different degrees of forest disturbance, and to determine their conservation potential. Methods: I compared the composition of insectivorous understory birds with the mist netting trap method. I characterized the habitats using the method of rectangular plots and based on the depth of the mulch, the luminosity, horizontal coverage of the vegetation of the understory, the forest basal area and the density of trees, palms and shrubs. Results: I captured a total of 397 individuals belonging to nine species. The mature forest was the habitat with the highest number of species (9) and individuals captured (139). Species composition varied significantly among habitats (F(2, 27)=3,8758, p<0,001). The species with the greatest weight in the dissimilarity between the habitats were: Sittasomus griseicapillus, Thamnophilusdoliatus and Eucometispenicillata. The assemblage of the species in the most disturbed habitats included more generalist species compared to the mature forest, where there was greater abundance of specialist species. The tree and palm density were the habitat attributes that best explained the association of the species (F(7, 22)=1,9774, rho=0,3794, p=0,003). There was no significant difference in the index of importance among the three habitats (ANOSIM, p=0,63330). Conclusion: Disturbed habitats are important for the conservation of some of the insectivorous bird species dependent on mature tropical forests.